Implementasi Prinsip Kehati-hatian Pada Tata Kelola Bank Syariah Indonesia - Ananda, Arini Shauba; Inayati, Anindya Aryu (Program Studi Ekonomi Syariah IAIN Parepare, 2024)
Prioritizing knowledge, abilities, and attitudes that sharia banking, including Bank Syariah Indonesia (BSI), must adopt is the foundation of the principle of prudence in banking governance. The objective of this study is to ascertain the degree to which BSI KCP Kajen applies the prudential principle. This study employs a qualitative methodology in the context of empirical law research. Two methods of gathering data were questionnaires and interviews. The study's findings show that BSI KCP Kajen has made an effort to incorporate the prudential principle into the framework for managing its operational system. This prudential principle has been put into practice by BSI through a pattern of transparency, asset quality, risk assessment, supervision, and compliance with legislation. According to data for 2022–2024, this has led to a rise in customer happiness, the reputation of banks, and the number of customers. The financial institution's stability and credibility can be sustainably maintained through the effective and efficient application of the prudential principle.